THE EFFECT OF USING QUIZZIZ MEDIA APPLICATION ON STUDENTS’ VOCABULARY MASTERY AT THE EIGHTH GRADE OF SMP SWASTA HKBP PADANG SIDEMPUAN IN 2022/2023 ACADEMIC YEAR - Sri Maharani Tanjung; Habib Rahmansyah; Kamisah Kamisah; Sri Indah Ananda Tamba (Institut Pendidikan Tapanuli Selatan, 2024)
The purpose of this research is to find: 1) the extent of application quizziz media application. 2) the extent of the students’ vocabulary mastery before and after using quizziz media application. 3) there is any significant effect of using quizziz media application on students’ vocabulary mastery at the eighth grade students of SMP Swasta HKBP Padang Sidempuan. That consist of 24 students. Then, the sample was 23 students which are taken by total sampling. The technique for collecting the data by observation sheet and giving test. After collecting, it was found that the score of application quizziz media application was 3,4. The mean score of students’ vocabulary mastery was 45,63. While the mean score of students’ vocabulary mastery after using quizziz media application was 82,13. The result data shows that the score of ttest was 4,47. The (df) was N-1 = 24 – 1 = 23. So, the researcher takes the score df of ttable at 5% significant level number 23 was 2,07. After finding the score ttest is the higher than ttable (ttest > ttable = 4,47>2,07). It means there was any significant effect of using Quizziz Media Application on Students’ Vocabulary Mastery at the VIII students of SMP Swasta HKBP Padang Sidempuan. So, hypothesis in this research can be accepted